GENDER AND GENDER EQUALITY IN THE CONTEXT OF LABOR LAW - Світовенко, Д. В. (Київський національний університет імені Тараса Шевченка, 2021)
The article reveals the actual essence of such phenomena as gender and gender equality inthe context of labor law of Ukraine. The author highlights the normative and theoreticalinterpretative approaches of scientists to understanding the concepts of “gender” and “genderequality”. Special attention is paid to the possibilities of understanding gender and genderequality in the sphere of work in the context of postmodern gender theory. It is proved that today,through the prism of labor law of Ukraine, gender acts as the roles of men and women defined bysociety and reflected in labor legislation in the field of labor and employment, which the legalnorm-maker considers appropriate for a man (male worker) and a woman (female worker) withoutthe purpose of discriminating against an able-bodied person. The author also substantiates thatgender equality in the context of labor law is the equal importance of men and women in the fieldof labor and employment, which is expressed in the mandatory provision of equal opportunitiesfor men and women in working life, equal access to resources and benefits in the field of labor andemployment, as well as in all spheres of personal life.

В статті з’ясовується актуальна сутність таких явищ, як гендер і гендернарівність в контексті трудового права України. Автором виокремлюються нормативні татеоретичні інтерпретаційні підходи вчених до розуміння понять «гендер» і «гендернарівність». Окрема увага приділяється можливостям осмислення гендеру та гендерноїрівності в сфері праці у контексті постмодерністської гендерної теорії. Доводиться, щосьогодні крізь призму трудового права України гендер постає в якості визначенихсуспільством та відображених у трудовому законодавстві ролі чоловіка та жінки в сферіпраці та зайнятості, які нормотворець без мети дискримінувати працездатну людинувважає належним для чоловіка (працівника) та жінки (працівниці). Також авторомобґрунтовується, що гендерна рівність в трудоправовому контексті – це однаковазначущість чоловіка та жінки в сфері праці та зайнятості, що виявляється в обов’язковупредставлені для чоловіка та жінки однакових можливостей в трудовому житті, рівногодоступу до ресурсів і благ у сфері праці та зайнятості, а також в усіх сферах особистого життя.
ГЕНДЕР І ГЕНДЕРНА РІВНІСТЬ В КОНТЕКСТІ ТРУДОВОГО ПРАВА
Keywords: discrimination; female worker; gender equality; gender; labor law; male worker; sphere of employment; sphere of labor.; гендер; гендерна рівність; дискримінація; працівник; працівниця; сфера зайнятості; сфера праці; трудове право.